2021
DOI: 10.1007/s12559-021-09819-8
|View full text |Cite
|
Sign up to set email alerts
|

Does Twitter Affect Stock Market Decisions? Financial Sentiment Analysis During Pandemics: A Comparative Study of the H1N1 and the COVID-19 Periods

Abstract: Investors are constantly aware of the behaviour of stock markets. This affects their emotions and motivates them to buy or sell shares. Financial sentiment analysis allows us to understand the effect of social media reactions and emotions on the stock market and vice versa. In this research, we analyse Twitter data and important worldwide financial indices to answer the following question: How does the polarity generated by Twitter posts influence the behaviour of financial indices during pandemics? This study… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(44 citation statements)
references
References 54 publications
0
30
0
4
Order By: Relevance
“…This study also found stronger effects on institutional investors than individual ones. Valle-Cruz et al. (2021) The Twitter data (the content of COVID-19) and important worldwide financial indices were used to examine whether they exhibit the relationship or not.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This study also found stronger effects on institutional investors than individual ones. Valle-Cruz et al. (2021) The Twitter data (the content of COVID-19) and important worldwide financial indices were used to examine whether they exhibit the relationship or not.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The COVID-19 crisis has created an unstable environment that has changed the sate of stock market aroung the world. Some authors compare the situation on the stock market with the effects of the H1N1 [5] from 11 years ago. The devastation in the global economy caused by the pandemic is shown on a scale not seen since the Great Depression [6], and thateven the Spanish flu did not have as much of an impact on the US stock market as COVID-19 [7].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Recent studies indicate that one of the main factors responsible for the variation in stock prices on the stock exchange is news related to the respective proprietary companies [6], [7], [8]. Adding more elements to the analysis is extremely important to build a balanced portfolio, and the sentimental analysis of the news shows positive results even during the COVID-19 [9] pandemic, a fact that destabilized the economy on a global scale and made the equity investment environment absolutely unstable.…”
Section: Introductionmentioning
confidence: 99%